Інституціоналізація електронної освіти у вищій школі України: переваги та ризики - Яковенко, Аліна Олегівна; Yakovenko, A. O. (Харків: ХНУ імені В.Н. Каразіна, 2021)
Yakovenko A. O. Institutionalization of e-learning in higher education in Ukraine: advantages and risks. – Qualification scholarly paper: a manuscript. Thesis submitted for obtaining the Doctor of Philosophy degree in Social and Behavioral Sciences, Speciality 054 – Sociology. – V. N. Karazin Kharkiv National University, Ministry of Education and Science of Ukraine, Kharkiv, 2021. Thesis is devoted to the sociological conceptualization of the phenomenon of e-learning, as well as to the elucidation of the state and features of its institutionalization in higher education in Ukraine. The urgency of the topic is due to new social needs and demands that are formed and caused by the processes of modernization and informatization of modern Ukrainian society, as well as global transformations caused by the coronavirus infection pandemic since 2019. Higher education institutions of Ukraine have faced new challenges that have forced them to consolidate their efforts to find the most effective ways to function and develop in the new environment - in the face of changing changes and constraints.
Institutionalization of e-learning in higher education in Ukraine: advantages and risks
Дисертаційна робота присвячена соціологічній концептуалізації феномену електронної освіти, а також з’ясуванню стану та особливостей її інституціоналізації у вищій школі України. Актуальність теми зумовлена новими соціальними потребами та запитами, які сформовані та викликані процесами модернізації та інформатизації сучасного українського суспільства, а також глобальними перетвореннями, які були спричинені пандемією коронавірусної інфекції, починаючи з 2019 року. Заклади вищої освіти України постали перед новими викликами, які змусили їх консолідувати свої зусилля задля пошуку найбільш ефективних шляхів свого функціонування та розвитку в нових умовах - в умовах мінливих змін та обмежень.
Keywords: електронна освіта; інституціоналізація; технології електронної освіти; електронний освітній простір; інформаційно-комунікативні технології; e-learning; institutionalization; e-learning technologies; e-learning space; information and communication technologies